2003
DOI: 10.1590/s0100-83582003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de nutrientes pelo cafeeiro sob interferência de plantas daninhas

Abstract: RESUMO -As plantas jovens de café são muito sensíveis à interferência das plantas daninhas, devido à forte competição por nutrientes que se estabelece entre essas plantas. Este trabalho teve como objetivo, portanto, avaliar os efeitos da interferência de sete espécies de plantas daninhas no conteúdo relativo (CR) de macro e micronutrientes, na massa seca da parte aérea de plantas de café. Aos 30 dias após o transplantio das mudas de café, em vasos contendo 12 L de substrato, fez-se o transplantio e/ou a semead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
34

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 6 publications
(5 reference statements)
2
27
0
34
Order By: Relevance
“…It suggests that those macronutrients were limited for coffee plant uptake and then influenced on coffee growth. Ronchi et al (2007) concluded that competition for nutrients reduced coffee initial growth, delaying plant establishment and maturity, but, according to Ronchi et al (2003), growth reduction intensity depended on the weed species. In general, weeds are more competitive for nutrients than crops (Ronchi et al, , 2007, suggesting that nutrition is an important factor in the evaluation of weed-crop interaction.…”
Section: Resultsmentioning
confidence: 99%
“…It suggests that those macronutrients were limited for coffee plant uptake and then influenced on coffee growth. Ronchi et al (2007) concluded that competition for nutrients reduced coffee initial growth, delaying plant establishment and maturity, but, according to Ronchi et al (2003), growth reduction intensity depended on the weed species. In general, weeds are more competitive for nutrients than crops (Ronchi et al, , 2007, suggesting that nutrition is an important factor in the evaluation of weed-crop interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Procedeu-se, portanto, para esta variável, apenas à análise descritiva, baseando-se no método usado por Ronchi et al (2003).…”
Section: Methodsunclassified
“…Sob densidade de cinco plantas por vaso de B. pilosa, o conteúdo relativo de nitrogênio, fósforo, potássio, cálcio e magnésio é cerca de 4, 14, 6, 7 e 9 vezes maior, respectivamente, nessa espécie do que na parte aérea de plantas de café cultivadas sem a interferência desta planta daninha (Ronchi et al, 2003). Além disso, Procópio et al (2004) verificaram que essa espécie apresenta elevada eficiência na utilização do nitrogênio absorvido, convertendo-o em biomassa.…”
Section: Introductionunclassified
“…Regarding the competition, Ronchi et al (2003) observed that the honey weed and other species of weeds caused a loss in the nutrient content of coffee plants, even in lower densities. Besides the interspecific competition, between coffee and honey weed, there is also the intraspecific competition, between individuals of the weed species (Ronchi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the interspecific competition, between coffee and honey weed, there is also the intraspecific competition, between individuals of the weed species (Ronchi et al, 2003). Ferreira et al (2011) noted that, in the second year of transition to organic coffee, honey weed was the most prevalent farming species, with a high relative density and abundance.…”
Section: Introductionmentioning
confidence: 99%